THE RIGHT TO SEXUAL AND REPRODUCTIVE HEALTH OF LGBTIQ PERSONS AND THE CHALLENGES OF BIOMEDICAL ASSISTED REPRODUCTION - Simić, Jelena (Pravni zapisi, 2022)
The mass application of modern medical biotechnology (BAF) and its expansion on a global level have brought numerous challenges at the individual and social level, and the very goal of reproductive technologies has exceeded the treatment of infertility. For LGBTIQ people, the use of BAF in the first place is a matter of reproductive justice that should provide everyone, without distinction, economic, social and political power and resources to make healthy decisions about their bodies, sexuality and reproduction for themselves, their families and their union. The reality, however, is that access to BAF is enjoyed by a small privileged group of people, and many medically infertile persons do not seek BAF because of the high cost of such treatment. As a result, the development of biomedical technology is increasingly becoming a subject of reconsideration and controversy, and less and less an achievement that supports life and health. In this paper, the author discusses when and why access to BAF became a matter of the LGBTIQ rights and whether access to BAF can really be equal for all, given its costs? Finally, the author refers to BAF in terms of domestic legislation and concludes the paper with a call for changes to the legal solution that prohibits the use of BAF for LGBTIQ individuals and couples in Serbia.